HADIS MARDŪD DAN DISKUSI TENTANG PENGAMALANNYA - H. Rajab (Jurnal Studi Islam, 2021)
This paper intends to explain the Mardud hadith and the discussion of scholars about its practice. Mardud hadith is a hadith that is rejected to serve as evidence and guidance in life. Even so, there are scholars who are tasahul in applying this provision, especially in cases related to fadail al-a'mal. This research is qualitative descriptive by relying on literature sources. The result of the research shows that all the hadiths of daif are mardud, which should be rejected as evidence in determining the law and refused to be practiced. The accusation that Ahmad bin Hanbal argues that the daif hadith can be practiced in the case of fadail is untrue and has been denied by his followers. The daif hadith he meant was the hasan hadith, which was unknown at that time. Regarding the hadith maudu', it is strictly agreed that it must be rejected, considering that it is a lie in the name of the Prophet and is threatened with hell in the hereafter. It's just that there are many "good sentences" that are spread in society, which are claimed to be the hadith of the Prophet. Some can be proven true, but some others are statements of certain people who are later declared to be from the Prophet. The best attitude towards "good sentences" like this is to examine who the first speaker is, then rely on the sentence on him, because if it is still relying on the Prophet, it will still be punished as maudu‘.